Impact of Work Task-Related Acute Occupational Smoke Exposures on Select Proinflammatory Immune Parameters in Wildland Firefighters. Issue 7 (July 2017) - Adetona, Anna M.; Adetona, Olorunfemi; Gogal, Robert M.; Diaz-Sanchez, David; Rathbun, Stephen L.; Naeher, Luke P.
Abstract : Objective: A repeated measures study was used to assess the effect of work tasks on select proinflammatory biomarkers in firefighters working at prescribed burns. Methods: Ten firefighters and two volunteers were monitored for particulate matter and carbon monoxide on workdays, January to July 2015. Before and after workshift dried blood spots were analyzed for inflammatory mediators using the Meso Scale Discovery assay, while blood smears were used to assess leukocyte parameters. Results: Firefighters lighting with drip-torches had higher cross-work-shift increases in interleukin-8, C-reactive protein, and serum amyloid A compared with holding, a task involving management of fire boundaries. A positive association between interleukin-8 and segmented-neutrophil was observed. Conclusion: Results from this study suggest that intermittent occupational diesel exposures contribute to cross-work-shift changes in host systemic innate inflammation as indicated by elevated interleukin-8 levels and peripheral blood segmented-neutrophils.